High-density lipoprotein enhancement of anticoagulant activities of plasma protein S and activated protein C - Griffin, John H.; Kojima, Kazuhisa; Banka, Carole L.; Curtiss, Linda K.; Fernández, José A. (The Journal of Clinical Investigation, 1999)
Low-density lipoprotein (LDL) and high-density lipoprotein (HDL) cholesterol levels are associated, respectively, with either increased risk or apparent protective effects for atherothrombosis. The ability of purified LDL and HDL to downregulate thrombin formation, a contributor to atherothrombotic processes, was assessed. Purified HDL, but not LDL, significantly enhanced inactivation of coagulation factor Va by activated protein C (APC) and protein S, and HDL stimulated protein S–dependent proteolytic inactivation of Va by APC, apparently due to cleavage at Arg306 in Va. In normal plasma, added HDL enhanced APC/protein S anticoagulant activity in modified prothrombin-time clotting assays. When the anticoagulant potency of HDL was compared with phospholipid (PL) vesicles of well-defined composition using this assay, HDL appeared qualitatively different from PL vesicles because HDL showed only good anticoagulant activity, whereas PL vesicles were rather procoagulant. When 20 normal plasmas were tested using this clotting assay, apoA-I levels correlated with anticoagulant response to APC/protein S (r = 0.47, P = 0.035), but not with activated partial thromboplastin time–based APC resistance ratios. Because HDL enhances the anticoagulant protein C pathway in vitro, we speculate that HDL may help downregulate thrombin generation in vivo and that this anticoagulant action is one of HDL's beneficial activities.